DESIGN OF TOURISM IN DKI JAKARTA HOMEPAGE USING HTML ROBOHELP - Roy Tumbay Bella; Aqwam Rosadi Kardian, Ir, MM Aqwam Rosadi Kardian, Ir, MM (Jurnal Sistem Informasi, 2001)
DKI Jakarta is the capital of the republic of Indonesia, but as the nation's capitalJakarta, is known not only as a center of government, but also a shopping andbusiness center.But besides the central government, entertainment, shopping and business, DKIJakarta, actually has the potential to become one of the tourist centers in the country,because adequate number of tourist attractions in Jakarta who deserve to be offered todomestic tourists and foreign tourists.Problems will arise if the attractions did not know by domestic and foreign touristswho want to come to Jakarta to see the tourist objects in jakarta. Problem-solving as awriter trying to implement RoboHelp HTML in the manufacture of tourismhomepages of DKI Jakarta, which has helped the tourists to get some importantinformation regarding the objects sights in Jakarta, the following description of thetourist objects.